Emerging roles of the RNA modifications N6-methyladenosine and adenosine-to-inosine in cardiovascular diseases - Vilbert Sikorski; Antti Vento; Esko Kankuri (Elsevier, 2022)
Cardiovascular diseases lead the mortality and morbidity disease metrics worldwide. A multitude of chemical base modifications in ribonucleic acids (RNAs) have been linked with key events of cardiovascular diseases and metabolic disorders. Named either RNA epigenetics or epitranscriptomics, the post-transcriptional RNA modifications, their regulatory pathways, components, and downstream effects substantially contribute to the ways our genetic code is interpreted. Here we review the accumulated discoveries to date regarding the roles of the two most common epitranscriptomic modifications, N6-methyl-adenosine (m6A) and adenosine-to-inosine (A-to-I) editing, in cardiovascular disease.